Meningkatkan Pembelajaran Pak Dengan Model Pbl Materi Terlibat Dalam Pelestarian Lingkungan Pada Siswa Kelas V SD - M. Cipy Olivia (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
This classroom action research aims to improve Catholic religious education learning using a problem based learning model with material involved in environmental conservation for class V students at SDN 39 Jelutung. In the context of the Merdeka curriculum, Catholic religious education in Indonesia is focused on developing religious understanding, moral values ​​and Catholic spirituality for students. The Merdeka curriculum places emphasis on the Pancasila student profile. In this class action research, the author focuses on the dimensions of faith, devotion to God Almighty and noble character which is based on the formation of strong character and mental attitudes in the younger generation, especially in facing complex global challenges. The students who attend SDN 39 Jelutung are students who mostly come from very simple families, with a distance of approximately 3-4 km to school, on foot. Apart from that, one of the problems faced by the world of education is the weak learning process because students are not directed enough to develop their thinking abilities, who only memorize the information given by the teacher. Students' brains are forced to remember and store various information. Classroom learning is more often teacher-centered, so students tend to be more passive in learning activities. Therefore, teachers can provide learning experiences by designing the learning process. One way is to apply the problem based learning (PBL) learning model. The Merdeka Curriculum as an alternative curriculum in overcoming learning setbacks is by preparing and implementing the learning process and developing a curriculum in schools that takes into account the needs and potential of students. The research was carried out using qualitative descriptive methods.